Whole genome sequencing analysis of avian infectious bronchitis virus isolated in Hung Yen province in 2021 - Roan, Do Thi; Khue, Nguyen Thi; Minh Duc, Luu; Thu Hien, Nguyen Thi; Thanh Hoa, Le; Hue, Le Thi; Kim Xuyen, Le Thi; Thanh Huong, Doan Thi (Vietnam Journal of Biotechnology, 2023)
Infectious bronchitis is an acute disease in chickens caused by the Infectious Bronchitis Virus (IBV). The disease causes serious economic losses in many countries in the world that have chicken farming industries. Even though vaccines have been used, the disease is still very complicated in many provinces and cities in Vietnam. The reason is that the virus strains causing the disease in the field have many changes compared to the vaccine virus strains. Research showed that there are numerous strains and genotypes of IBV in Vietnam. However, only the S1 gene has been studied, and no research has been done on the full genome. In this study, the IBV strain causing disease in 2021 in Hung Yen Province (North Vietnam) was sequenced and analyzed for molecular characteristics. The analysis results showed that strain IBHYM belongs to genotype QX-like (GI-19) and has a close relationship with Chinese IBV strains. The IBHYM strain has higher nucleotide and amino acid similarities with strains of genotype QX-like (87.5% to 95% for nucleotide and 80.2% to 91.3% for amino acid) and the lowest similarity to strains of genotype TC07-like (70.4% to 70.5% for nucleotide and 53.8% to 56.2% for amino acid). The field pathogenic virus strains also have low nucleotide and amino acid similarity with the Massachusetts vaccine strain currently in use (86% for nucleotide and 77.1% for amino acid). Research results show the importance of molecular epidemiological surveillance and the selection of appropriate vaccine strains in Vietnam. This is the first report of sequencing the whole IBV genome in Vietnam.